S30 Does Obesity Make For Worse Childhood Asthma?. (19th November 2012) - Turner, SW; Mehta, A; Ayres, JG; Palmer, CN; Mukhopadhyay, S
Abstract : Introduction: Obesity may be important to asthma causation but the relationship between obesity and outcomes within populations of children with established asthma is inconsistent across studies. This study tested the hypothesis that obese children who have asthma have worse asthma outcomes in comparison with non-obese, non-overweight children with asthma. Methods: Cross-sectionally, children with asthma were recruited from hospitals across Scotland using published methods.1 A respiratory questionnaire and quality of life questionnaire (PAQLQ) were completed with measured height, weight, spirometry and exhaled NO. Obesity was defined as body mass index (BMI) >95th% and non-obese or overweight as BMI<85th%. Asthma outcomes were categorised as severity (emergency prednisolone treatment, BTS treatment step, spirometry) and control (PAQLQ). Results: There were 693 children recruited in whom BMI was determined in 501 including 103 who were obese and 71 overweight (ie BMI >85th% but ≤95th%). In unadjusted comparisons and compared to non-obese non-overweight children, obese children had higher %FVC (mean difference 6.0% [95% CI 0.7, 11.2] p=0.026), reduced %FEV1/FVC (mean difference 4.5% [95% CI 1.2, 7.8] p=0.007), a trend for lower PAQLQ score (4.8 versus 5.8, p=0.071) and were less likely to have co-existent eczema or hayfever (OR 0.8 [0.7, 0.9] p=0.001). In the multivariate analysis and compared with non-obese non-overweight children, obese children had reduced %FEV1/FVC and also reduced risk for eczema or hayfever but not for other outcomes. Conclusion: This is the first study of associations between obesity and asthma outcomes in a UK paediatric population. Although children with asthma may have slightly different physiology (i.e., obstructed lung function and reduced atopy) compared to non-obese, non-overweight individuals, these differences are unlikely to be of clinical relevance. Weight reduction interventions targeted specifically at obese children with established asthma are unlikely to improve asthma severity or control. References: Turner et al . A methodology to establish a database to study gene environment interactions for childhood asthma. BMC Medical Research Methodology, 2010, 10–107.